2017
DOI: 10.1016/j.celrep.2017.03.036
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-Specific Differentiation Is Influenced by State of Human Pluripotency

Abstract: Human pluripotent stem cells (hPSCs) have been reported in naive and primed states. However, the ability to generate mature cell types remains the imperative property for utility of hPSCs. Here, we reveal that the naive state enhances self-renewal while restricting lineage differentiation in vitro to neural default fate. Molecular analyses indicate expression of multiple lineage-associated transcripts in naive hPSCs that failed to predict biased functional differentiation capacity. Naive hPSCs can be converted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 68 publications
3
34
3
Order By: Relevance
“…LIF-3i reversion of a broad repertoire of non-diseased conventional, primed hiPSC and human embryonic stem cells (hESC) decreased lineage-primed gene expression, and diminished the interline variability of directed differentiation typically observed amongst independent primed, conventional hPSC lines 12,13 . In contrast to reports of difficult directed differentiation of human naïve states 25,26 , LIF-3i-reverted N-hiPSC differentiated directly to all three germ layer lineages with significantly higher efficiencies and more rapid kinetics of differentiation than their isogenic primed hiPSC counterparts. This high multi-lineage differentiation potency of tankyrase/PARP inhibited N-hPSC did not require either basic FGF supplementation in undifferentiated cultures, or an additional re-priming or capacitation culture step to enable differentiation competence 25,26 .…”
Section: Resultscontrasting
confidence: 96%
“…LIF-3i reversion of a broad repertoire of non-diseased conventional, primed hiPSC and human embryonic stem cells (hESC) decreased lineage-primed gene expression, and diminished the interline variability of directed differentiation typically observed amongst independent primed, conventional hPSC lines 12,13 . In contrast to reports of difficult directed differentiation of human naïve states 25,26 , LIF-3i-reverted N-hiPSC differentiated directly to all three germ layer lineages with significantly higher efficiencies and more rapid kinetics of differentiation than their isogenic primed hiPSC counterparts. This high multi-lineage differentiation potency of tankyrase/PARP inhibited N-hPSC did not require either basic FGF supplementation in undifferentiated cultures, or an additional re-priming or capacitation culture step to enable differentiation competence 25,26 .…”
Section: Resultscontrasting
confidence: 96%
“…S1; see Methods). In contrast to reports of difficult directed differentiations of human naïve states, or requirement for culture back to a primed pluripotent state 25, 26 , LIF-3i-reverted N-hiPSC differentiated directly to all three germ layer lineages with significantly higher efficiencies and more rapid kinetics of differentiation than their isogenic primed, conventional hiPSC counterparts. This high multilineage differentiation potency of N-hPSC did not require an additional 're-priming' culture step.…”
Section: Lif-3i Naïve Reversion Of Conventional Primed Hipsc Lines Scontrasting
confidence: 77%
“…Recent reports showed that some human naïve PSC lines are lineage biased and fail to differentiate towards mature cell types 39,40 , thus limiting their use for disease modelling and developmental studies. We tested the differentiation potential of 3 isogenic niPSC lines (HPD01, HPD03 and HPD04) to gauge the technical variability of our reprogramming system, and included a primed iPSC line (HPD00) as a control.…”
Section: Characterization Of the Differentiation Potential Of Nipscsmentioning
confidence: 99%